PENGARUH PEMBERIAN SERESAH DAN CACING TANAH TERHADAP PERTUMBUHAN TANAMAN LAMTORO (Leucaena leucocephala Lam De Wit) DAN TURI (Sesbania grandiflora) PADA MEDIA TANAM TANAH BEKAS PENAMBANGAN BATU BARA - Wiryono Wiryono (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2006)
The objectives of this study was to evaluate the effects of earthworm introduction and leaf litter on the soil fertility and plant growth on the coal-mined soil growth media. This factorial experiment used completely randomized design. The first factor was the type of growth media, consisting of four levels, namely 1) topsoil, 2) coal-mined soil, 3) coal- mined soil + leaf litter of Euphatorium odoratum, and 4) coal-mined soil, + Euphatorium litter + earthworms, Pontoscolex corethrurus. The second factor was plants species, consisting of two levels, namely 1) Sesbania grandiflora and 2) Leucaena leucochepala Lam De Wit. Results showed that addition of leaf litter, or addition of leaf litter plus earthworms significantly increased soil fertility and plant growth. Sesbania gradiflora significantly grew faster thanLeucanea leucocephala.